The business of love: how matchmaking thrives in Singapore - Chia, Brandon Bing Xuan (Nanyang Technological University, 2023)
Physical matchmaking agencies remain alive and well in Singapore despite the rise of online dating. Both formal and informal matchmakers continue to serve well-educated singles in their mid-twenties to fifties who have trouble finding "the one". In the 2021 Marriage and Parenthood Survey, 80 per cent of the singles, age 21 to 35, have aspirations of marriage but 50 per cent were not actively dating at the time and 38 per cent had not even dated before. Our package examines how matchmakers operate, the cost of their service, feedback from single men and women, success couples and other niche matchmaking services within smaller communities in Singapore.